2009
DOI: 10.2174/1874210600903010154
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Bleeding on Probing and Subgingival Deposits. An Endoscopical Evaluation

Abstract: Background:Bleeding on probing (BOP) is an indicator of tissue inflammatory response to bacterial pathogens. Due to anatomical limitations, the entity and physical state of microbial aggregations located under the gingival margin and their relations to BOP have been hardly investigated till now. The recent introduction of the endoscopy has allowed clinicians to observe the subgingival environment in a non-traumatic way. The aim of this study is to evaluate the correlation between BOP and subgingival deposits b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
2
44
1
4
Order By: Relevance
“…In addition to the dental restoration variable, BOP was added as a potential confounder when the outcome variable was AL or PD. Checchi et al 41 demonstrated a direct relationship between BOP and the presence/amount of subgingival deposits. Low systemic BMD was significantly associated with severe AL after controlling for BOP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dental restoration variable, BOP was added as a potential confounder when the outcome variable was AL or PD. Checchi et al 41 demonstrated a direct relationship between BOP and the presence/amount of subgingival deposits. Low systemic BMD was significantly associated with severe AL after controlling for BOP.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 This parameter is associated with the presence of biofilm and subgingival calculus, 17 and has been used to indicate the need for subgingival intervention. 18,19 During periodontal maintenance, BoP and probing pocket depth (PPD) are used as prognostic factors for future periodontal disease activity.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Для предварительной диагно-стики использовались: зондирование ПК по 3 точкам зон-дом по Williams [1], определение патологической подвиж-ности зубов по Флезару [9]; данные ОПТГ. Для уточнения диагноза у всех пациентов исследовали глубину ПК (по Рамфьерду) [2] под контролем эндоскопа с помощью эн-доскопической системы Perioscopy (Perioscopyinc) [15,24,28,29]. Так же была проведена КЛКТ (фирма производи-тель VATECH, Южная Корея).…”
Section: материал и методыunclassified
“…В ка-честве методик сравнения во всех случаях использовались стандартизированные клинические методики: КЛКТ (Vatech) и эндоскопическая диагностика (Perioscopy) [13,15,16,[21][22][23].…”
Section: материал и методыunclassified